Cultural differences in sports fan engagement on Facebook: a comparison of Australian and Indian cricket league. (24th February 2022) - Annamalai, Balamurugan; ShabbirHusain, R.V.; Chandrasekaran, Shabana; Varshney, Sanjeev
The study explores the impact of cultural differences on social media fan engagement depending on the post content shared on social media. The differential impact on fan engagement with regard to team performance is also explored. Around 1, 500 Facebook posts across four cricket teams from the cricket leagues of Australia and India were evaluated. Analysis of variance was used to test the effect of the post content, team performance, and cultural differences on affective fan engagement. First, fans are likelier to have higher engagement with posts that deal with individual sports person than the team and this effect is more pronounced in countries with higher power distance. Second, our study has established that fans are likelier to have higher engagement with better performing teams and this effect is more pronounced in countries with higher collectivism. This is the first study to explore the cultural differences and the impact of player versus team-related content types on social media engagement metrics in sports fan engagement. The study results have direct implications on developing the social media content strategy for sports clubs across different cultures.